Hellboy II [videorecording (DVD)] : the golden army - Toro, Guillermo del, 1964-; Mignola, Mike; Perlman, Ron, 1950-; Blair, Selma, 1972-; Jones, Doug, 1960-; Tambor, Jeffrey, 1944-; Hurt, John, 1940-2017; MacFarlane, Seth, 1973- (Universal Studios Home Entertainment, 2008)
The fate of mankind hangs in the balance when a ruthless prince awakens an unstoppable army of creatures and wages war with the human world. It's up to Hellboy and his team of paranormal outcasts to face off with the forces of darkness.